2023
DOI: 10.5812/aapm-129532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laryngeal Mask Airway on Image Quality in Pediatric Patients Undergoing Brain Magnetic Resonance Imaging: A Randomized Controlled Trial

Abstract: Background: Magnetic resonance imaging (MRI) is highly sensitive to motion, resulting in artifacts and lowering image quality. Laryngeal mask airway (LMA) provides numerous advantages over endotracheal tubes as it reduces laryngospasm, coughing, and the risk of postoperative desaturation. Objectives: We aimed to compare LMA with oral airway for airway management during brain MRI in terms of reducing motion artifacts, which can improve image quality. Methods: This randomized, controlled, double-blind trial was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…However, a randomized controlled trial showed a higher likelihood of vocal cord injury when using I-gel compared to air-Q [93]. From a clinical point of view, SAD can be an option for airway maintenance in high-risk pediatric patients during anesthesia [94,95].…”
Section: Special Patientsmentioning
confidence: 99%
“…However, a randomized controlled trial showed a higher likelihood of vocal cord injury when using I-gel compared to air-Q [93]. From a clinical point of view, SAD can be an option for airway maintenance in high-risk pediatric patients during anesthesia [94,95].…”
Section: Special Patientsmentioning
confidence: 99%